Lyle, Lyle, crocodile storybook treasury - Waber, Bernard (Houghton Mifflin Harcourt, 2012)
Lyle and the birthday party: Lyle the crocodile becomes so jealous of Joshua's birthday party and presents that it makes him feel ill, and he ends up in the hospital, where he recovers his good nature by entertaining the children there.